Chemical Vapor Transport Deposition of Stable Cubic CsPbI3 Optical Films on the Porous Alumina Substrate. (2019) - Zhao, Cong; Zhao, Shichao; Zhao, Yuanfang; He, Fang; Luo, Ripeng; Li, Jingzhou; Zhao, Shixi; Wei, Guodan; Kang, Feiyu
ABSTRACT: Cesium lead iodide perovskite (CsPbI3 ) with excellent optical and electrical properties have attracted numerous academic attentions. Specifically, the black cubic phase CsPbI3 with a direct band gap of 1.74 eV has been most appropriate materials for various optoelectronic applications, especially for photovoltaic (PV), Light-Emitting Diodes (LED) and photodetector applications1. However, the preferred cubic phase of bulk CsPbI3 (α-CsPbI3 ) is usually only stable at high temperatures and it will undergo an immediate phase transformation to orthorhombic phase (δ-CsPbI3 ) after fabrication at room temperature. In this work, we have discovered a convenient CVD method to investigate the growth behavior of the cubic α-CsPbI3 film on the porous alumina substrate. The lead iodide and cesium iodide were used as the precursors for the deposition of CsPbI3 . The porous alumina with high surface area and large pore volume was used as growth substrate. It was shown that the porous alumina promoted the growth of CsPbI3 film by absorbing the precursor and increasing the nucleation density. The prepared CsPbI3 film emitted strong and stable red light under ultraviolet light excitation at room temperature and ambient atmosphere. The lead iodide was absorbed on the surface of the porous alumina firstly then reacted with cesiumiodide to form the CsPbI3 . The successful preparation of the CsPbI3 by the direct CVD method paves the way for its large scale growth and application in optoelectronic devices.